Determinants of Employee Attitudes and Behavior To Use Employee Self-Service App - Arafa , Aninda Zakia; Dwi Lestari, Setyani; Sofiani, Fenti; Sugiarto, Dadet (Universitas Trisakti, 2024)
This study explores the influence of perceived usefulness, perceived ease of use, perceived organizational support, and management pressure on attitudes and behavioral intentions to use Metrodata's Employee Self-Service (ESS). In today's digital workplace, technology adoption is critical to improving productivity and efficiency. This study aims to understand how these four factors influence employee attitudes and behaviors in the context of Metrodata Mobile ESS. This study involved 200 employees of PT Metrodata Electronics, Tbk. This study uses the Modified Technology Acceptance Model (TAM) which has been modified to assess the impact of Perceived Usefulness, Perceived Ease of Use, Perceived Organizational Support, and Management Pressure on employee attitudes and intentions to use the Metrodata ESS Mobile application. The results showed that each variable that is Perceived Usefulness, perceived ease of use, perceived organizational support, and management pressure has a positive and significant influence on Attitude and Behavioral Intention to Use. The findings of this study provide valuable insight into the factors that encourage or hinder the adoption of Metrodata Mobile ESS within the company PT Metrodata Electronics Tbk. Understanding these influences is critical to designing effective strategies in promoting technology adoption and increasing its use in the workplace, ultimately contributing to improved efficiency, productivity, and company performance.